Universitas Kristen Satya Wacana, Jalan Diponegoro No. 52 - 60, Kel. Salatiga, Kec. Sidorejo, Kota Salatiga, Prov. Jawa Tengah - Billy Gustav Theodore; Hanna Prillysca Chernovita (Journal on Education, 2024)
Travel in Marau sub-district is a company that operates in the transportation services sector, which is located precisely in Suka Karya village, Marau sub-district, Ketapang city, West Kalimantan. This company provides travel, car rental and goods delivery services. However, in conducting business, this company has not implemented or involved IS/IT in running its existing business. So, when carrying out company operations, it is recommended to carry out information system strategic planning, this aims to assist in the preparation of information systems so that later they can gain profits and are in line with the company's business objectives. This writing method uses qualitative, with data collection carried out by observation, interviews, observation and research using the Ward and Peppard method and analyzed using SWOT, Value Chain, Five Porter's, Mc Farlan's Strategic Grid. From the results of the research that has been carried out, there are 5 recommendations in the proposed application portfolio, namely. Recording and bookkeeping using Word and Excel which was previously done manually, using a website-based travel service information system to make things easier for consumers, carrying out promotions via social media to reach more consumers, using an Asset Management Information System and cashiers in carrying out management and operations.